الصورة البيانية اللّونية في شعر محمود سامي البارودي - رشيد, أ.م.د. آزاد عبدول; محمد, سامان عبدالجبار (Sulaimani Journal for Humanities, 2023)
This research (the chromatic image in Mahmoud Sami Al-Baroudi’s poetry) aims to identify the nature of the chromatic image in Mahmoud Sami Al-Baroudi’s poetry, and that we cannot understand from the chromatic image unless we meditate, delve, analyze and infer the poetic verses that carry the connotation of the chromatic graph, and through our interaction With the text in the process of clarifying the graphic images and revealing their pictorial meanings, and this is what enables us to reach the picture that the poet drew in the color graphic image to express what is inside of the statement of colors to complete the artistic painting. The chromatic graphic image occupies a large area in Mahmoud Sami Al-Baroudi's Diwan, and we notice it abundantly in similes, metaphors, and metonymy.
Keywords: Keywords Color image; Histogram